“Return to life’’ in Quran, Traditions and Wisdom with emphasis on the Views of Allameh Tabatabai - Enayatollah Sharifi; khavaninzadeh Mohammad Hossein (پژوهش نامه معارف قرآنی, 2015)
Believing in “Return to life’ is one of the certain beliefs of the Shia so that the Shia scholars have claimed to have reached a consensus on this issue and it is argued and cited to verses 82 and 83 Surah Naml (the ant), verses 55, 72, 254, 259 of Surah Baqarah and verse 43 of Surah Sâd for the possibility of their occurrence. Alsonumeroustraditions imply the possibilityoftheirreturn to life repeatedly.Some of them are entered about the importance and greatness of the day return, somein interpretation ofthe verses about returnandothersabout recent return. The most ofrationalreasons about the possibility of occurrence of return are inherentrefusal andthe possibility of occurrence,philosophicalrule or principleofoccurrence of anything and concept of “what is permissible and what is not permissible, are unit’’.